Biocompatibility and biomineralization assessment of mineral trioxide aggregate flow - Bueno, Carlos Roberto Emerenciano [UNESP]; Vasques, Ana Maria Veiga [UNESP]; Cury, Marina Tolomei Sandoval [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP] (Springer Nature, 2018)
Objective: Evaluate, in vivo, the biocompatibility via subcutaneous inflammatory tissue response and mineralization ability of the new MTA Flow compared to MTA Angelus and ProRoot MTA. Materials and methods: Forty male Wistar rats were assigned and received subcutaneous polyethylene tube implants containing the test materials and a control group with empty tube (n = 10 animals/group). After days 7, 15, 30, and 60, the animals were euthanized and the polyethylene tubes were removed with the surrounding tissues. Inflammatory infiltrate and thickness of the fibrous capsule were histologically evaluated. Mineralization was analyzed by Von Kossa staining and under polarized light. Data were analyzed via Kruskal-Wallis and Dunn’s test with a significance level of 5%. Results: MTA Angelus induced the mildest reaction after 7 (P > .05) and 15 days (P < .05) followed by MTA Flow, both cements achieving mild inflammatory reaction after 15 days. ProRoot MTA induced a severe inflammation on day 7 and was reducing after day 15 (P > .05). No difference was observed after days 30 or 60 (P > .05). Von Kossa staining and birefringent structures were positive to all materials. Conclusions: At the end of the experiment, the novel MTA Flow showed biocompatibility and induced biomineralization in all time periods. Clinical relevance: The final consistence obtained in MTA Flow may facilitate several procedures, indicating that the MTA Flow has a promising application in endodontics.
Keywords: Biocompatibility; Biomineralization; Inflammation; Mineral trioxide aggregate